Reducing Greenhouse Gas Emissions through Community-based Action: an Analysis of the Program Kampung Iklim in Indonesia - Fatkhullah, Mukhammad; Pamungkas, Nugroho Rinadi; Habib, Muhammad Alhada Fuadilah; Mulyani, Iwed (Asean Social Work Journal, 2023)
One strategy to deal with climate change is accelerating greenhouse gas (GHG) emissions reduction through a community-based approach. In Indonesia, the government pursues community engagement to reduce GHG emissions through the Program Kampung Iklim (ProKlim). We collected data from 2015-2018, then measured emission reductions (ER) in the waste, livestock, agriculture, energy, and forestry sectors by subtracting baseline and mitigation emissions. The analysis compares the emission reductions achieved through Community-based Action (CBA) to the national emission reduction achievement. The results show that the sector with the most participation rates and the most significant contributor to emission reductions in ProKlim is the energy and waste sector. On the other hand, the sectors that attract the least public attention and emission reduction are the livestock and agriculture sectors. Through 61 community groups and 138 actions, from 2015 to 2018, CBA contributed 133,312.38 tons of CO2e emission reductions, 0.012% to national emission reductions, with the participation value equivalent to USD$266.080. Based on this number, CBA can be the answer to Indonesia's low position in international carbon trading. A strategy that focuses on increasing community participation is needed to optimize the contribution of the CBA to large-scale national emission reductions.